Pengembangan Media Belajar Kegawatdaruratan Maternal Atonia Uteri Berbasis E-Learning - Rahajeng Siti Nur Rahmawati (Akademi Keperawatan Dharma Husada Kediri, 2017)
The research objective of this development is to get an overview of media development study maternal emergencies atonic-based e-learning (mobile aplication). The development model used in this study using the 4D model Thiagarajan modified. Three early stage in the procedure through which the 4D development in this study is a Define (definition), Design (planning) Develop (development). Media Mobile Learning is assessed by 1 application specialists, 1 specialist emergency, and 40 D-IV Midwifery students to determine the response of students. The instrument used in the form of a questionnaire. Applications developed contains six main menu, namely the theory, clinical and diagnosis, action, checklist, video, exercises and about the application. Keywords: mobile apps, media, emergency maternal atonic